The Legal Certainty in the Application of Sanctions for the Abuse of Narcotics Class I Not Derived from Plants Based on the Principle of Justice (A Study of Decision Number: 528/Pid.Sus/2025/PN Tjk) - Jainah, Zainab Ompu; Ramadan, Suta; Ningrum, Intan Putri Yani Cahya; Anggara, Firga Fiksona (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Class I narcotics crimes that are not plants are serious crimes that have a wide impact on public health, security, and order, and threaten the future of the nation's generation. One of the important problems in handling narcotics crimes is ensuring legal certainty in the application of criminal sanctions to perpetrators who commit acts without rights and against the law. The problems raised are: Legal Certainty in the Application of Sanctions Without Rights and Against the Law on Class I Narcotics Crimes that are not Plants Based on Decision Number 528 / Pid.Sus / PN Tjk. and What are the factors causing perpetrators to commit Class I narcotics Abuse based on the principle of justice. The research method uses a normative and empirical juridical approach. The normative juridical approach is taken through a literature study by examining relevant laws and regulations, doctrines, and legal literature. Meanwhile, the empirical approach is carried out by interviewing parties involved or directly understanding the case to obtain a factual picture regarding the application of the law in the field. The results of the study indicate that the application of criminal sanctions to the defendant in Decision Number 528/Pid.Sus/2025/PN Tjk has fulfilled the principle of legal certainty, especially regarding the fulfillment of the elements of